THE TEXTBOOK DEVELOPMENT OF MATHEMATICS LEARNING STRATEGY BASED ON KKNI CURRICULUM - Sehatta Saragih (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2017)
AbstractThe development of curriculum is parallel to the development of Science and Technology, and requires the support of learning resources in order the appointed competence could sustain the optimization of the accomplishment of reliable human resourcers in facing life requirement which become more complex day by day. The textbook as one of the learning resources where its contents adapted from curriculum should be available in order the efforts of competency accomplishment could realized optimally. From those rationales, the researcher as the lecturer of the mathematics learning strategy tried to develop a textbook through a research. The aim of this research is to produce a valid and practical textbook of mathematics learning strategy in order it is feasible to be used as a textbook. In developing this textbook, the researcher used 4-D frame model. The results of this research show: (1) validity tests by the experts is in a high validity category; (2) reliability tests is in an excellent category; (3) the practicality test is in a practical category.Keywords: the textbook development, validity, reliability, and practicalityAbstrakPerkembangan kurikulum sejalan dengan perkembangan IPTEK dan perlu dukungan sumber belajar agar kompetensi yang ditetapkan dapat menopang optimalisasi pencapaian SDM yang handal dalam menghadapi tuntutan kehidupan yang semakin kompleks. Buku ajar sebagai salah satu sumber belajar yang muatannya disesuaikan dengan kurikulum sebaiknya tersedia agar upaya pencapaian kompetensi dapat terelaisasi dengan optimal. Berangkat dari rasional tersebut maka peneliti sebagai pemangku matakuliah Strategi Pembelajaran Matematika, mencoba mengembangkan buku ajar melalui sebuah penelitian. Tujuan penelitian ini adalah menghasilkan buku ajar pada matakuliah Strategi Pembelajaran Matematika yang valid dan praktikal sehingga layak digunakan sebagai buku sumber. Dalam pengembangan buku ajar ini peneliti menggunakan model kerangka 4-D. Hasil penelitian menunjukkan : (1) ujivaliditas pakar berada pada kategori sangat valid; (2) uji kelayakan berada pada kategori sangat baik; (3) uji praktikalisasi berada pada kategori praktis.Kata Kunci: Pengembangan Buku Ajar, Validitas, Kelayakan dan Praktikalitas